2009
DOI: 10.1080/16506070802561256
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability of Computer-Aided Cognitive Behavioural Therapy: A Pragmatic Study

Abstract: The clinical and cost-effectiveness of a computer-aided cognitive behavioural therapy (CCBT) programme, Beating the Blues, is indicated by a number of studies, but relatively little is known about its acceptability for patients with depression, anxiety, or both. This study investigated the acceptability of Beating the Blues offered on eight scheduled clinic visits with brief face-to-face support. Pre and posttreatment measures explored the relationship among programme acceptability, treatment continuation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…This is comparable with other Internet-based samples for prolonged grief, PTSD [19,22] and other mental disorders [60,61,62,63]. In fact, Internet-based interventions seem as yet unable to rise to the challenge of engaging less well-educated people [64].…”
Section: Discussionmentioning
confidence: 48%
“…This is comparable with other Internet-based samples for prolonged grief, PTSD [19,22] and other mental disorders [60,61,62,63]. In fact, Internet-based interventions seem as yet unable to rise to the challenge of engaging less well-educated people [64].…”
Section: Discussionmentioning
confidence: 48%
“…This is a controversial topic on which the literature is not conclusive (e.g., Whitfield & Williams, 2004;Cavanagh et al, 2009). We hypothesized that expectations and satisfaction would be high for all three treatment conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents were asked if they were hypothetically interested in using various resources, but it may have been hard for them to envision these resources and decide if they would indeed be helpful. Research has indicated that the opportunity to view a demonstration of online mental health resources enhances the credibility and acceptability of those resources among potential participants [18,19] , therefore it is possible that we may have obtained a more accurate measure of interest by showing respondents examples of relevant resources.…”
Section: Discussionmentioning
confidence: 99%